Ethanol-tolerant pickering emulsion stabilized by gliadin nanoparticles. (1st June 2022) - Xu, Wei; Sun, Haomin; Kang, Mengyao; Zheng, Shuqing; Ning, Yuli; Jia, Yin; Hu, Yuling; Luo, Denglin; Zhang, Chunlan
Abstract: In this paper, ethanol-tolerant Pickering emulsion was prepared using gliadin nanoparticles (NPs) based on pH adjustment coupled heat treatment. The effects of gliadin NPs concentration on ethanol-tolerant Pickering emulsions in terms of emulsion size, microstructure, and rheology were investigated. The results indicated that gliadin NPs exhibited an elliptical appearance. At pH 7, the particle size was 600.04 ± 4.80 nm, and the polydispersity coefficient was 0.18 ± 0.29. Fluorescence spectra showed that this method destroyed the tertiary structure of the protein and initiated the self-assembly of gliadin. With the increase of particle concentration, the size of the Pickering emulsion decreased, and the emulsion gradually became gelatinized. The increase of particle concentration made the oil-water interface in emulsion more robust. This study showed that the preparation of gliadin NPs based on pH regulation coupled heat treatment could stabilized the emulsion in the presence of ethanol. The structural and functional properties of Pickering emulsion could be regulated by the concentration of particle stabilizers, thus providing a theoretical basis for constructing structured and functionalized Pickering emulsions. Highlights: Gliadin nanoparticles were prepared using pH adjustment coupled heat treatment. Ethanol-tolerant Pickering emulsion were prepared using gliadin nanoparticle. Structural and functional properties of Pickering emulsion can be regulated by concentration of particle stabilizers.